x2+3x+1 = 0
Using the quadratic equation formula gives you:
(x+2.618033989)(x+0.3819660113) = 0
So: x = -2.618033989 or x = -0.3819660113
-2
x2 + 3x + 7 = 5 ∴ x2 + 3x + 2 = 0 ∴ (x + 1)(x + 2) = 0 ∴ x ∈ {-2, -1}
X2 + 3X = 0X(X + 3) = 0--------------------X is the greatest common factorso,X = 0----------orX = - 3----------- assuming you might want to solve this type of problem some day
3x-1 = 11 3x = 11+1 3x = 12 x = 4 Therefore: x2+2 = 18
-2x + 3x = -4 By combining like terms we get: x = -4.
x2 plus 3x plus 3 is equals to 0 can be solved by getting the roots.
x2 + 3y = 7 3x + y2 = 3 3y = x2 + 7 y2 = -3x + 3 y = x2/3 + 7/3 y = ± √(-3x + 3) If you draw the graphs of y = x2/3 + 7/3 and y = ± √(-3x + 3) in a graphing calculator, you will see that they don't intersect, so that the system of the given equations has not a solution.
-2
x2 + 3x + 7 = 5 ∴ x2 + 3x + 2 = 0 ∴ (x + 1)(x + 2) = 0 ∴ x ∈ {-2, -1}
x = 2
x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0
X2 + 3X = 0X(X + 3) = 0--------------------X is the greatest common factorso,X = 0----------orX = - 3----------- assuming you might want to solve this type of problem some day
3x-1 = 11 3x = 11+1 3x = 12 x = 4 Therefore: x2+2 = 18
-2x + 3x = -4 By combining like terms we get: x = -4.
x=-11
is a quadratic equation for y, in terms of x.
1 and 2